Historical analysis of inter-regional migration in the Philippines - Bernardo, Thelma S. 1955- (1982)
This study focuses on the patterns of inter-regional migration patterns for the 1970-1975 period. The historical perspective of the study takes into consideration earlier patterns of movement in the Philippines, specifically the 1939-1970 period, to analyze the changes in population distribution over time.
Two methods of estimating migration were utilized: the direct estimate based on the residence method and the indirect estimate based on the census survival ratios. Comparison of estimates derived from the two methods show that some differences in migration volume and patterns exist. It appears that the more appropriate method of estimating migration in the Philippine context is the residence method.
Historical analysis show that majority of the region during the period 1939-1975 did not change their status as in-migration and out-migration areas. Persistence of the general pattern of movement, that is, towards the vicinity of the greater Metropolitan area and the frontier regions of Mindanao were observed from 1939-1975. However, some changes were observed notably for Cagayan Valley and western Mindanao which
changed their status from in-migration to out-migration areas. On the other hand, Central Luzon which has been an out-migration area in the past, was an in-migration area during the more recent period (1970-1975).
Age and sex selectivity of migrant still prevailed even up to 1975. Majority of the migrants were found in the younger age groups: females in all regions of the country appeared more migratory than males. The result of this study corroborates earlier findings – that the direction of movement tends to be from the less developed to the more progressive areas. Such
pattern of movement subtly indicates an imbalance in regional development. The socio-economic available amenities in the more developed planners should therefore address this imbalance in the distribution of development benefits and population, if the overall objective of equity is to be achieved.
Mimeographed.
Vita.
Thesis
Keywords: Migration, Internal -- Philippines